Haloterrigena sp. Strain SGH1, a Bacterioruberin-Rich, Perchlorate-Tolerant Halophilic Archaeon Isolated From Halite Microbial Communities, Atacama Desert, Chile - Flores, Nataly; Hoyos, Sebastián; Venegas, Mauricio; Galetović, Alexandra; Zúñiga, Lidia M.; Fábrega, Francisca; Paredes, Bernardo; Salazar-Ardiles, Camila; Vilo, Claudia; Ascaso, Carmen; Wierzchos, Jacek; Souza-Egipsy, Virginia; et al. (Frontiers in Microbiology, 2020)
An extreme halophilic archaeon, strain SGH1, is a novel microorganism isolated from endolithic microbial communities colonizing halites at Salar Grande, Atacama Desert, in northern Chile. SGH1 could grow at maximal concentrations of 0.5 M magnesium chloride or 0.15 M perchlorate and, accumulates bacterioruberin (BR) whose isomers were nontoxic to human cells. Our study provides structural, biochemical, genomic and physiological information on this new isolate living at the edge of the physical and chemical extremes at the Atacama Desert. SGH1 is a Gram-negative, red-pigmented, non-motile unicellular coccoid. Under the transmission electron microscope, strain SGH1 showed an abundant electro-dense material surrounding electron-lucent globular structures resembling gas vacuoles. Strain SGH1 showed a 16S rRNA gene sequence with a close phylogenetic relationship with the extreme halophilic archaea Haloterrigena turkmenica and Haloterrigena salina and has been denominated Haloterrigena sp. strain SGH1. Strain SGH1 grew at 20-40°C (optimum 37°C), at salinities between 15-30% (w/v) NaCl (optimum 25%) and growth was improved by addition of 50 mM KCl and 0.5 % w/v casamino acids. Growth was severely restricted at salinities below 15% NaCl and cell lysis is avoided at a minimal 10% NaCl. Maximal concentrations of magnesium chloride and sodium or magnesium perchlorates that supported SGH1 growth were 0.5 M and 0.15 M, respectively. Haloterrigena sp. strain SGH1 accumulates bacterioruberin (BR), a C50 xanthophyll, as the major carotenoid. Total carotenoids in strain SGH1 amounted to nearly 400 µg BR per gram of dry biomass. Nearly 80% of total carotenoids accumulated as geometric isomers of BR: all-trans-BR (65%), 9-cis-BR (10%), 13-cis-BR (4%); other carotenoids were dehydrated derivatives of BR. Carotenogenesis in SGH1 was a reversible and salt-dependent process; transferring BR-rich cells grown in 25% (w/v) NaCl to 15% (w/v) NaCl medium resulted in depigmentation, and BR content was recovered after transference and growth of unpigmented cells to high salinity medium. Methanol extracts and purified BR isomers showed an 8-9-fold higher antioxidant activity than Trolox or β-carotene. Both, plasma membrane integrity and mitochondrial membrane potential measurements under acute 18-hour assays showed that purified BR isomers were nontoxic to cultured human THP-1 cells.